Perspectivas docentes sobre la implementación del enfoque orientado a la acción en entornos rurales: Estudio de caso único - Roberto Rojas-Alfaro; Ana Marcela Montenegro Sánchez (Actualidades Investigativas en Educación)
This case study investigates the implementation of the action-oriented approach (AoA) within rural primary schools in Costa Rica, focusing particularly on its adaptation and challenges in socioeconomically disadvantaged areas. Using a qualitative case study design, semi-structured interviews were conducted with two English as a foreign language teachers and a rural primary school principal during June and July 2023. Prior to the interviews, informed consent was obtained from the participants. The interviews explored how the AoA helps teachers facilitate the curriculum and the contextual factors affecting its implementation. For data analysis, thematic analysis was employed, and the information was validated with participants. The study identifies significant barriers, including socioeconomic disparities affecting student behavior, limited professional development for teachers, and the limited relationship between parents and the school. These findings are crucial as they highlight the need for specific AoA adaptations and emphasize the necessity for targeted professional development and improved communication strategies with parents. The study contributes to the sparse literature on AoA in Spanish-speaking rural contexts and underscores the need for changes in educational policy for the effective implementation of such educational innovations.